ID: 131. Issue 1 (November 2015) - Poelzl, Andrea; Prchal-Murphy, Michaela; Rom, Rita; Kaufmann, Therese; Lassnig, Caroline; Mueller, Mathias; Strobl, Birgit
<x xml:space="preserve">Abstract</x> Sepsis is initiated by the presence of bacteria, or their products (e.g. endotoxins), in the bloodstream. It still represents a major problem in health care due to high mortality rates and incomplete understanding of the molecular mechanisms driving the disease. The Janus kinase Tyk2 is part of the signal transduction cascade utilized by different cytokines that are crucial for innate and adaptive immune responses. We have reported previously that absence of Tyk2 in mice leads to an increased resistance against lipopolysaccharide (LPS)-induced endotoxin shock. Within this study, we show that mice expressing kinase-inactive Tyk2 (Tyk2K923E) show an intermediate resistance against LPS between Tyk2 knockout mice (Tyk2−/−) and wildtype (WT) mice. Systemic levels of pro-inflammatory cytokines, such as IL-1<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7rpw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives>, IL-17A, IL-6 and IL-18, were decreased in Tyk2−/− and Tyk2K923E compared to WT mice, suggesting that kinase-independent functions of Tyk2 affect either local or late-stage immune responses. IFN<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7pvm" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives>/<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7rpw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives> and IFN<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7kx5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives> production as well as IFN<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7pvm" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives>/<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7rpw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives> responsiveness were strongly impaired in both Tyk2−/− and Tyk2K923E mice. In line with this, activation of STAT1/2/3/4 in response to IL-12 and IFN<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7rpw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives> was similarly impaired in Tyk2−/− and Tyk2K923E NK cells and macrophages, respectively. Thus kinase-independent functions of Tyk2 are likely not connected to Tyk2's function in IL-12 and IFN<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7pvm" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives>/<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7rpw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives> signalling cascades. In addition to the kinase-independent functions of Tyk2, we provide evidence for a kinase-dependent involvement of Tyk2 in the regulation of the early hypothermic response to LPS. We are currently investigating late-stage immune responses and organ pathology. This project is funded by the <funding-source id="gp005" xlink:type="simple" xlink:role="http://www.elsevier.com/xml/linking-roles/grant-sponsor" xlink:href="" xmlns:xlink="http://www.w3.org/1999/xlink">Austrian Science Fund</funding-source> (FWF, grants <award-id rid="gp005" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">P25642-B22</award-id> and <award-id rid="gp005" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">SFB-F28</award-id>).